Respiratory kinematic and airflow differences between reflex and voluntary cough in healthy young adults - Brandimore, Alexandra E.; Troche, Michelle S.; Huber, Jessica E.; Hegland, Karen W. (Frontiers in Physiology, 2015)
Background: Cough is a defensive behavior that can be initiated in response to a stimulus in the airway (reflexively), or on command (voluntarily). There is evidence to suggest that physiological differences exist between reflex and voluntary cough; however, the output (mechanistic and airflow) differences between the cough types are not fully understood. Therefore, the aims of this study were to determine the lung volume, respiratory kinematic, and airflow differences between reflex and voluntary cough in healthy young adults. Methods: Twenty-five participants (14 female; 18-29 years) were recruited for this study. Participants were evaluated using respiratory inductance plethysmography calibrated with spirometry. Experimental procedures included: 1) respiratory calibration, 2) three voluntary sequential cough trials, and 3) three reflex cough trials induced with 200 µM capsaicin. Results: Lung volume initiation (LVI; p=.003) and lung volume excursion (LVE; p<.001) were significantly greater for voluntary cough compared to reflex cough. The rib cage and abdomen significantly influenced LVI for voluntary cough (p<.001); however, only the rib cage significantly impacted LVI for reflex cough (p<.001). LVI significantly influenced peak expiratory flow rate for voluntary cough (p=.029), but not reflex cough (p=.610). Discussion: Production of a reflex cough results in significant mechanistic and airflow differences compared to voluntary cough. These findings suggest that detection of a tussigenic stimulus modifies motor aspects of the reflex cough behavior. Further understanding of the differences between reflex and voluntary cough in older adults and in persons with dystussia (cough dysfunction) will be essential to facilitate the development of successful cough treatment paradigms.